Podcast-Based Learning in EFL Classrooms: Enhancing Junior High School Students’ Listening Skills and Motivation - Wawang Santika Agustini; Rahmat Budiman; Bachtiar Bachtiar (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the effectiveness of podcast-based learning in enhancing junior high school students’ listening skills and learning motivation in the Indonesian EFL context, where learners often have limited exposure to authentic spoken English and low engagement in listening activities. An explanatory sequential mixed-methods design was employed involving 68 ninth-grade students from a junior high school in West Java, Indonesia, who were assigned to experimental and control groups. Quantitative data were collected through listening pre-tests, post-tests, and motivation questionnaires, while qualitative data were obtained through semi-structured interviews. The findings revealed that the experimental group achieved significantly higher listening gains than the control group. ANCOVA results confirmed a significant effect of podcast-based learning on listening achievement (F = 39.4, p 0.001, η² = 0.377), indicating a large effect size. Students also reported increased motivation, confidence, enjoyment, and engagement. Interview data further showed that podcasts provided authentic listening input, enhanced vocabulary and pronunciation awareness, and promoted learner autonomy. Overall, podcast-based learning offers an effective, authentic, and learner-centered approach to improving listening proficiency and motivation in secondary EFL education.